Sycamore Row - Grisham, John (Hodder & Stoughton, 2013)
Jake Brigance has never met Seth Hubbard, or even heard of him, until the old man's suicide note naes him attorney for his estate. The will is dynamite. Seth has left ninety percent of his vast, secret fortune to his housemaid. The vultures are circling even before the body is cold: the only thing more incendiary than money in Ford County is race, and this case has both. As the relatives contest thewill, Jake searches for answers to the many questions left by Seth Hubbard's death...